2015
DOI: 10.6116/kjh.2015.30.4.101.
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Effects of Hydroponic-cultured Ginseng Folium by fermentation

Abstract: Objectives : Positive effects of Ginseng has great research attentions such as anticancer, anti-diabetic, antiaging, liver, immune function, CNS, etc. In this study, we investigated Hydroponic-cultured Ginseng Folium fermented by Bacillus subtilis to establish fermentation conditions for enhancing functionality.Methods : Ginseng Folium were cultivated hydroponic-cultured and were extracted with methanol. We inoculate Bacillus subtilis for fermentation by adding to 0%, 3% and 5% sugar respectively and checked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, the short-term cultivation of a hydroponic culture results in a higher content of ginsenosides in the roots and leaves [ 40 ]. Hydroponic-cultured ginseng saponins have antioxidant [ 39 ], anti-inflammatory [ 41 ], hepatoprotective [ 42 ], and immunomodulatory activities [ 43 ], but there is no scientific evidence that hydroponic cultured fresh ginseng root is pharmacologically efficacious against lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the short-term cultivation of a hydroponic culture results in a higher content of ginsenosides in the roots and leaves [ 40 ]. Hydroponic-cultured ginseng saponins have antioxidant [ 39 ], anti-inflammatory [ 41 ], hepatoprotective [ 42 ], and immunomodulatory activities [ 43 ], but there is no scientific evidence that hydroponic cultured fresh ginseng root is pharmacologically efficacious against lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Panax ginseng (Korean ginseng) is a plant under the family Araliaceae distributed in 35 countries as an herbal medicine for over 2000 years [ 18 ]. Ginseng contains more than 100 bioactive components known as ginsenoside [ 19 ], which has already been proven to have anti-inflammatory [ 20 ], antioxidant [ 21 ], and hepatoprotective [ 22 ] activities, but there is no evidence for wastewater treatment. This study highlighted hydroponically cultured ginseng, and it has been reported that hydroponically cultured ginseng leaves contain a significantly higher amount of ginsenosides than root and stem [ 23 ].…”
Section: Introductionmentioning
confidence: 99%